Prognostic Factors of Survival in Pancreatic Cancer Metastasis to Liver at Different Ages of Diagnosis: A SEER Population-Based Cohort Study - Liu, Meiqi; Wang, Moran; Li, Sheng (Frontiers in Big Data, 2021)
Background Liver is a common metastatic organ for most malignancies, especially the pancreas. However, evidence for prognostic factors of pancreatic cancer metastasis to the liver at different ages is lacking. Thus, we aimed to evaluate the predictors of patients with pancreatic cancer metastasis to liver grouped by age of diagnosis. Methods We chose the patients diagnosed between 2004 and 2015 from the SEER database. The primary lesions of metastatic liver cancer between sexes were compared using the Pearson’s chi-square test for categorical variables. The overall survival (OS) and cancer-specific survival (CSS) were the endpoint of the study. The prognostic factors were analyzed with the Kaplan-Meier method and log-rank test, and Cox proportional-hazards regression model. Results The main primary sites of metastatic liver cancer for our patients are lung and brunchu, sigmoid colon, pancreas, which in males are lung and bronchu, sigmoid colon and pancreas, while breast, lung and bronchu, sigmoid colon in females. Furthermore, we explored the prognostic factors of pancreatic cancer metastasis to liver grouped by age at diagnosis. Tumor grade, histology and treatment are valid prognostic factors in all age groups. Additionally, gender and AJCC N stage in age<52 years old, while race and AJCC N stage in age>69 years old were predictors. Surgery alone was the optimal treatment in group age>69 years old, whereas surgery combined with chemotherapy was the best option in the other groups. Conclusion Our study evaluated the predictors of patients with pancreatic cancer metastasis to liver at various ages of diagnosis.